Peranan Kepemimpinan Dalam Memberikan Dorongan Kepada Anggota Tim Untuk Meningkatkan Hasil Kerja Mereka Adalah Hal Yang Sangat Penting Dalam Meningkatkan Produktivitas Kerja. - Juniarmi, Intan (Maneggio, 2024)
The study was conducted at Bungo Plaza Hotel located in Muara Bungo, Jambi, spanning one month, specifically in March 2017. Its objective was to examine how leadership contributes to motivating employees to enhance their productivity at Bungo Plaza Hotel. Findings indicate that leaders play a crucial role in boosting work productivity directly through their active involvement, recognizing that enhanced productivity is pivotal for goal achievement. The strong rapport between supervisors and subordinates is evidenced by the attention given to suggestions and ideas from the latter, guidance provided by superiors, and feedback—whether praise, criticism, or warnings—used as forms of motivation in line with governmental policies to foster employee discipline and productivity. Additionally, superiors' decisions to acknowledge outstanding employees significantly influence motivation levels among the workforce. These decisions serve as a technique within the leadership style to inspire employees. However, leaders encounter challenges in tailoring motivation strategies to align with employees' diverse traits and preferences, making it challenging to cater to their individual needs effectively. Moreover, employees' reluctance to openly express their concerns poses a barrier that leaders must address, alongside addressing any job dissatisfaction among employees.